PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, PERCEIVED RISK IMPACT TO LECTURERS’ INTERNET BANKING ADOPTION - Langelo, Andretha S. E. (Universitas Sam Ratulangi, 2013)
The development of Information Technology that are now spreading on banking sector, indirectly has met some of customers’ lifestyle who are more inclined want everything was instant and efficient, it is because of demands of times and work which makes them have to be able to do other things, but can still do their work simultaneously. But in terms deciding to buy product/service that relate to information tecnology, people have consideration, wheter about the usefulness, ease of use and risk. The purpose of this study was to find out the relationship between perceived usefulness, perceived ease of use, perceived risk on internet banking adoption especially to customer that are lecturers of faculty of economics and business. This research is a quantitative research that use casual type of research. The data was collected through questionnaire with sample size is about 40 lecturers who are selected using sampling insidental method and analyzed by multiple linear regression analysis method. The conclusion is there is significant positive effect between perceived usefulness, perceived ease of use and perceived risk towards Internet banking adoption. It means banks should improve the performance of internet banking services in order to more provide meaningful benefits for users and improve the security of transactions through Internet banking services to increase the adoption of Internet banking service. Therefore the researcher recommended to the bank to better understand the needs of their customers in order to deliver services more effective. Keywords: perceived usefulness, perceived ease of use, perceived risk, internet banking adoption.